2022
DOI: 10.1038/s41584-022-00867-4
|View full text |Cite|
|
Sign up to set email alerts
|

Glycobiology of rheumatic diseases

Abstract: Glycosylation has a profound influence on protein activity and cell biology through a variety of mechanisms, such as protein stability, receptor interactions and signal transduction. In many rheumatic diseases, a shift in protein glycosylation occurs, and is associated with inflammatory processes and disease progression. For example, the Fc-glycan composition on (auto)antibodies is associated with disease activity, and the presence of additional glycans in the antigen-binding domains of some autoreactive B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 170 publications
0
14
0
1
Order By: Relevance
“…Finally, the Ge and Se granules each hosted ∼200 N -glycoproteins carrying predominantly oligomannosidic- and less sialylated/fucosylated complex-type N -glycans. While traditionally regarded as an intracellular glyco-feature pertaining to immaturely-processed N -glycoproteins trafficking the secretory machinery, oligomannosylation is increasingly reported i) on mature (fully processed) neutrophil glycoproteins as comprehensively reviewed 4,20 , ii) to decorate the surface of neutrophils 41 and other blood 42 and epithelial 43,44 cells, and iii) to be elevated in cancer 45,46 and other neutrophil-related diseases 47 . Our study supports that oligomannosylation is a prominent feature of the Ge and Se compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Ge and Se granules each hosted ∼200 N -glycoproteins carrying predominantly oligomannosidic- and less sialylated/fucosylated complex-type N -glycans. While traditionally regarded as an intracellular glyco-feature pertaining to immaturely-processed N -glycoproteins trafficking the secretory machinery, oligomannosylation is increasingly reported i) on mature (fully processed) neutrophil glycoproteins as comprehensively reviewed 4,20 , ii) to decorate the surface of neutrophils 41 and other blood 42 and epithelial 43,44 cells, and iii) to be elevated in cancer 45,46 and other neutrophil-related diseases 47 . Our study supports that oligomannosylation is a prominent feature of the Ge and Se compartments.…”
Section: Discussionmentioning
confidence: 99%
“…It thus comes as no surprise that defects in protein glycosylation are associated with a variety of diseases. We direct the reader to excellent reviews on glycosylation in cancer [ 43 , 44 , 45 , 46 , 47 , 48 ], neurodegenerative disorders, including Alzheimer’s disease, Parkinson’s disease, autism spectrum disorder, and schizophrenia [ 49 , 50 , 51 ], congenital disorders [ 52 , 53 ], infection, and inflammation [ 54 , 55 , 56 , 57 , 58 ]. To understand how the nature and conformation of the glycan can drastically change the interaction of a protein with another in the context of health and disease, we direct the reader to several review articles [ 47 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, it has been extensively studied and shown that IgG-Fc glycan composition is highly variable and changes with age, sex, health, and disease 4 , 6 , 7 . Specific IgG-Fc glycosylation patterns lacking terminal galactoses have been identified, for example, in rheumatic (e.g., rheumatoid arthritis, systemic lupus erythematosus, and ANCA-associated vasculitis) and other inflammatory diseases and are clearly associated with inflammation and disease activity 8 . In addition, alterations in Fc glycosylation have recently been highlighted in studies of anti-spike protein IgG responses in patients with COVID-19, showing highly dynamic glycosylation patterns, including low core fucosylation that correlates with disease severity 9 – 11 .…”
Section: Introductionmentioning
confidence: 99%